The Effects of Brewing Condition on Tea's Caffeine Content and Sensory Quality - Lembono, Pilandari; Mulyanto, Catherine Theodora; Michelle, Michelle; Kurniawan, Yosia Gabriel (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Tea is a widely consumed beverage in Indonesia due to its distinctive flavor and bioactive compounds, including caffeine and antioxidants. This study aimed to evaluate the effects of brewing temperature and time on caffeine content and sensory acceptability, and to determine the optimal brewing conditions for green and black tea. Indonesian green tea and black tea were brewed at temperatures of 60, 70, 85, and 95 °C for 2, 5, 7, and 10 minutes using a tea-to-water ratio of 1.85 g per 250 mL of water. Caffeine content was determined using UV-Vis spectrophotometry, while sensory evaluation was conducted through a hedonic test to assess consumer preference. The results showed that higher brewing temperatures and longer steeping times increased the extraction of caffeine and antioxidants in both green and black tea. However, these conditions tended to reduce sensory acceptability. Therefore, the optimal brewing conditions were determined by balancing chemical extraction with sensory preference. For green tea, the optimal condition was identified as brewing at 85 °C for 7 minutes, producing a caffeine content of 312.51 ppm and an average hedonic score of 2.78 on a 5-point scale. For black tea, the optimal brewing condition was also 85 °C for 7 minutes, yielding a caffeine content of 283.86 ppm and a hedonic score of 3.93. These findings provide practical guidance for optimizing tea brewing conditions to achieve desirable sensory quality while maintaining beneficial bioactive compounds.